2020
DOI: 10.1155/2020/1607141
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus Endocarditis Complicated by Pauci-Immune Necrotizing Glomerulonephritis

Abstract: Infective endocarditis (IE) is more common in patients with predisposing cardiac lesions and has many potential complications, including stroke and arterial thromboembolisms. Renal manifestations have an estimated prevalence of ∼20%. Rapidly progressive glomerulonephritis (RPGN) is a nephrological emergency manifested by autoimmune-mediated progressive loss of renal function over a relatively short period of time. Here, we report the case of a 60-year-old Caucasian male, who presented with speech impairment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The retrospective studies of Arbarillo et al, Nwanyanwu et al and Yelin et al [60,61,62] suggested that the true prevalence of infections caused by lactobacilli is higher than estimated only on the basis of case reports. In addition, in many of the reports analyzed here it was stated that lactobacilli are often disregarded as infective agents since they are considered culture contaminants [29,40,61].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The retrospective studies of Arbarillo et al, Nwanyanwu et al and Yelin et al [60,61,62] suggested that the true prevalence of infections caused by lactobacilli is higher than estimated only on the basis of case reports. In addition, in many of the reports analyzed here it was stated that lactobacilli are often disregarded as infective agents since they are considered culture contaminants [29,40,61].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli were isolated from blood [15,16,17,18,20,21,22,23,24,25,26,27,29,30,31,32,33,34,35,36,37,38,40,41,42,43,44,45,46,47,49,52,55,56,57], diseased valve tissue [28], abscess fluids [48,51,52,54,57,58], cerebrospinal fluid (CSF) [46], marrow [36], arthrocentesis aspiration fluid [53] in anaerobiosis and, in some cases, also in aerobiosis [40,15]. Use of automated microbial detection system, i.e.…”
Section: Cases Of Lactobacilli Infections Reported In Years 2019 2020...mentioning
confidence: 99%
See 2 more Smart Citations
“…Lactobacilli were isolated from blood [ 15 , 16 , 17 , 18 , 20 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 52 , 55 , 56 , 57 ], diseased valve tissue [ 23 ], abscess fluids [ 48 , 51 , 52 , 54 , 57 , 58 ], cerebrospinal fluid (CSF) [ 46 ], marrow [ 30 ], arthrocentesis aspiration fluid [ 53 ] in anaerobiosis and, in some cases, also in aerobiosis [ 15 , 34 ]. Use of automated microbial detection system, i.e., BACT/ALERT 3D or the BACTEC systems (BioMérieux) with incubation at 35 °C were mentioned in some reports [ 23 , 31 , 34 ].…”
Section: Cases Of Lactobacilli Infections Reported In Years 2019 2020...mentioning
confidence: 99%